Effective Interpersonal Communication for Foreign Managers to Indonesian - CO Workers - Respati Wulandari (Binus Business Review, 2014)
Interpersonal communication tends to guide the way of management in companies worldwide. For multinational company, where expatriate is exist to blend with local partners or employee, the way they communicate to each other will determine the future of their company communication activities. The result of this research could be utilized by foreign managers and their Indonesian colleagues. Based on this research, which is supported by qualitative and literature methods, it can be found the effective method of communication to enhance job performance. The purpose of qualitative method that used by the author is to gain much information from employees and foreign managers in several companies. Besides interviewing them, author also joined in their interpersonal. The effective way of interpersonal communication to improve employee working performance is to form a sharing forum, informal meetings or communities of practice.